Psychological and Social Status of Children Treated with Renal Dialysis and their Mothers at Tanta City (International Journal of Nursing Education, 2020)
Background and Aim: Renal dialysis treatment of children with end-stage kidney disease (ESKD) posesvarious challenges including financial difficulties, social challenges and psychological problems. Parentsfrequently face financial difficulties as they require more time off work and cannot work overtime. Sicknessof a child causes a decline in the financial and socioeconomic status of the family and also hampers itsfunctionality. Moreover, care for those children involves considerable psychological and social stress. Thisstudy aimed to assess psychological and social condition of children treated with renal dialysis and theirmothers.Materials and Method: The research was conducted on children with End-stage renal disease (ESRD)treated with renal dialysis and their mothers. The total studied population in this study was 40 child andtheir mothers (N= 40). One tool was used to collect data about the children illness and socio-demographiccharacteristics. Children psychological and social status is assessed using the Paediatric Quality of LifeInventory (PedsQL)and their parents the PedsQL-proxy version. Mothers health, social, and psychologicaldata were collected using General Health Questionnaire (GHQ-12), and Berlin Social Support Scales(BSSS).Result: Children psychological and social status were significantly low as reported by the children or themothers who provide primary care for APD children. The mothers perceived available and actually receivedsupport is low. Overall score of General Health Questionnaire of the mothers was very high by median andquartile 17 (15–18).Conclusions: Children psychological and social status were low according to PedsQL test. The family ofchildren with renal dialysis need financial support. Mothers who provide primary care to children on renaldialysis require emotional support and assistance in self fulfillment. The mothers have high GHQ-12 scoringwhich means that they are have greater chance for increase of non-psychotic mental disorders. There is astrong need to provide continuous psychological care for caregivers.